2018
DOI: 10.1093/schbul/sby144
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation Improves Semantic Speech–Gesture Matching in Patients With Schizophrenia Spectrum Disorder

Abstract: Background Patients with schizophrenia spectrum disorders (SSD) have severe deficits in speech and gesture processing that contribute considerably to the burden of this disorder. Brain imaging shows left inferior frontal gyrus involvement for impaired processing of co-verbal gestures in patients with schizophrenia. Recently, transcranial direct current stimulation (tDCS) of the left frontal lobe has been shown to modulate processing of co-verbal gestures in healthy subjects. Although tDCS has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…Conclusions from this study are however limited by the low number of participants and their divergent disease stage (3 out 6 were chronic rather than acute/ subacute stroke patients). In line with our study, just recently, facilitatory effects of cathodal tDCS on gesture processing were found in schizophrenia, further underlining the validity of using non-invasive brain stimulation methods to improve gesture performance [47].…”
Section: Discussionsupporting
confidence: 91%
“…Conclusions from this study are however limited by the low number of participants and their divergent disease stage (3 out 6 were chronic rather than acute/ subacute stroke patients). In line with our study, just recently, facilitatory effects of cathodal tDCS on gesture processing were found in schizophrenia, further underlining the validity of using non-invasive brain stimulation methods to improve gesture performance [47].…”
Section: Discussionsupporting
confidence: 91%
“…Nonverbal trainings are rare in the field of psychiatry. One study executed no training, but could show positive effects of transcranial direct current stimulation (tDCS) on gesture integration in a group of patients with schizophrenia spectrum disorder (68). Another study could show a benefit from single session transcranial magnetic stimulation (TMS) also for gesture production in patients with schizophrenia (69).…”
Section: Current Treatments For Patients With Schizophreniamentioning
confidence: 99%
“…been successfully applied in a large number of fMRI (14-16, 84), EEG (85), tDCS (68,86) and patient studies including patients with schizophrenia (30,31). Altogether, we use six categories of videos in our study: videos containing.…”
Section: Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent study found that for healthy individuals, anodal tDCS (atDCS) over the motor cortex improved semantic word retrieval performance (Martin et al, 2017). In terms of gesture comprehension, studies have used tDCS over the IFG to investigate the role of this region in processing gestural-verbal stimuli (Cohen-Maximov et al, 2015; Schulke and Straube, 2017, 2018). Gesture prime clips were implemented for word targets.…”
Section: Introductionmentioning
confidence: 99%